STUDI KUALITATIF: PERAN AHLI GIZI DALAM KEPATUHAN DIET DIABETESI (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Dietary regulation affects blood glucose levels, however, the dietary compliance of patients with Diabetes Mellitus (DM) in Indonesia is still low. One factor that influences the dietary adherence of DM patients is the support of a nutritionist. This study aimed to describe the role of nutritionists in diet compliance with Type-2 DM. This study is qualitative research with a narrative approach. Six Type-2 DM informants have been selected according to the inclusion criteria which were then triangulated with five informants. Triangulation was carried out to ensure the validity of the data. Data has been collected by using in-depth interviews. The results showed that the role of nutritionists as an educator and a counselor who carried out the standardized nutrition care processes have a critical effect on dietary compliance. The optimal complieance can be embended by collaboration with other health care members while also built a good relationship with patient's families. This research recommended that increased knowledge and skills of nutritionists can be part of optimize the implementation of the role so as to improve patient's dietary compliance.